Explainable AI (XAI) driven skin cancer detection using transformer and CNN based architecture - Radiah, Faiza; Rahman, Kabasum; Asadullah, Lasania; Sohan, Md. Sohanur Rahman; Ahmed, Jaki (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.